2014
DOI: 10.3732/ajb.1300428
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, phylogenetic, and ecological diversity of the new model species Setaria viridis (Poaceae: Paniceae) and its close relatives

Abstract: SETARIA VIRIDIS is a diploid species and has contributed to several polyploid derivatives. The most morphologically similar of the polyploids is S. faberi, which differs in spikelet features, phylogenetics, genome size, and ecological response to drought. Researchers using field-collected S. viridis as a model organism will benefit from the clear delimitation provided in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 32 publications
2
31
0
Order By: Relevance
“…However, most primer sets failed to amplify or produced weak and/or complex patterns in S. pumila. This is in agreement with the results of phylogenetic analyses that place S. viridis, S. italica and one genome of the tetraploids S. faberi and S. verticillata into a single clade while S. pumila is more distantly related Layton and For each marker, the allele (in bp) that is present at a frequency of [50 % in one of the subpopulations and \5 % in both other subpopulations is indicated as specific alleles (Spe) a The chromosomal location was obtained by conducting a Blastn search of the primer sequences listed in Jia et al (2009) against the S. italica genome sequence (Bennetzen et al 2012) Kellogg 2014). Our analysis of 30 S. pumila accessions with 11 SSR markers yielded no evidence of gene flow between S. pumila and S. viridis growing in sympatry.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…However, most primer sets failed to amplify or produced weak and/or complex patterns in S. pumila. This is in agreement with the results of phylogenetic analyses that place S. viridis, S. italica and one genome of the tetraploids S. faberi and S. verticillata into a single clade while S. pumila is more distantly related Layton and For each marker, the allele (in bp) that is present at a frequency of [50 % in one of the subpopulations and \5 % in both other subpopulations is indicated as specific alleles (Spe) a The chromosomal location was obtained by conducting a Blastn search of the primer sequences listed in Jia et al (2009) against the S. italica genome sequence (Bennetzen et al 2012) Kellogg 2014). Our analysis of 30 S. pumila accessions with 11 SSR markers yielded no evidence of gene flow between S. pumila and S. viridis growing in sympatry.…”
Section: Discussionsupporting
confidence: 81%
“…It may have spread in the US along the railroads, and became a major agricultural problem in the Corn Belt in the 1950s (Knake 1990). Morphologically, S. faberi is very similar to and easily confused with S. viridis (Fairbrothers 1959;Layton and Kellogg 2014). The characteristics that best distinguish the two species are the greater length ratio of the lemma and 2nd glume in S. faberi compared to S. viridis, and the pubescence on the upper surface of the leaf blades of S. faberi.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Mutant populations have been characterized in both foxtail millet and green foxtail millet, and the identity of candidate genes was revealed by novel high-throughput sequencing approaches (Li et al, 2016; Liu et al, 2016; Martins et al, 2016; Xue et al, 2016). S. italica and S. viridis have been used in the characterization of important agronomic traits, including yield-related architectural traits such as height, branching, biomass, flowering time and domestication-related traits such as shattering (Qian et al, 2012; Jia et al, 2013; Mauro-Herrera et al, 2013; Wang et al, 2013; Doust et al, 2014; Gupta et al, 2014; Layton and Kellogg, 2014; Qie et al, 2014; Fahlgren et al, 2015; Fang et al, 2016; Hodge and Kellogg, 2016; Liu et al, 2016; Mauro-Herrera and Doust, 2016). …”
mentioning
confidence: 99%
“…(green foxtail) is a member of the Panicoideae subfamily and is a close relative of several major forage and bioenergy grasses. Due to its C 4 carbon fixation pathway, diploid nature, short life cycle and relatively small genome (~510 Mb), green foxtail has been rapidly adopted as a model for investigations the genetic of the biofuel crop switchgrass and for C 4 photosynthesis (Doust et al, 2009;Brutnell et al, 2010;Li, Brutnell, 2011;Layton, Kellogg, 2014). Ghannoum (2009) has indicated that C 4 plants may by similarly or even more sensitive in comparison with C 3 plants but the response of C 4 plants to drought stress has not been so well studied as response of C 3 plants and it is important to understand how drought stress influences the photosynthesis in C 4 plants.…”
Section: Introductionmentioning
confidence: 99%